Microwave dielectric material, preparation method thereof and electronic component

By combining calcium aluminum borosilicate glass and SiO2, microwave dielectric materials with low dielectric constant, high quality factor and near-zero temperature coefficient of resonant frequency were prepared, solving the problem of limited material performance in existing technologies and achieving improved stability and energy efficiency for high-frequency applications.

CN121449409APending Publication Date: 2026-02-03SHENZHEN SUNLORD ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511576678.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing microwave dielectric materials, while reducing dielectric constant, struggle to maintain high quality factor and precisely control resonant frequency temperature coefficient, resulting in limitations on system stability and energy efficiency.

Method used

By combining calcium aluminum borosilicate glass, SiO2, and specific additives, and controlling the proportions of each component, microwave dielectric materials with low dielectric constant, high quality factor, and near-zero temperature coefficient of resonant frequency are prepared. Calcium aluminum borosilicate glass is used as a doping agent, SiO2 is used as the host material, and additives such as B2O3, Li2O, Al2O3, ZnO, and TiO2 are used to adjust the material properties.

Benefits of technology

Microwave dielectric materials with low dielectric constant, low dielectric loss, and near-zero frequency temperature coefficient have been developed, making them suitable for high-frequency applications, reducing system energy loss, and ensuring frequency stability of devices over a wide temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of electronic materials, and provides a microwave dielectric material, a preparation method thereof and an electronic component. The microwave dielectric material is prepared from the following raw materials in percentage by weight: 5wt%-20wt% of calcium-aluminum-boron glass, 60wt%-85wt% of SiO2 and 2wt%-15wt% of an additive, wherein the total weight percentage of the calcium-aluminum-boron glass, the SiO2 and the additive is 100%; wherein the additive comprises at least one of B2O3, Li2O and Al2O3, and at least one of ZnO and TiO2. The microwave dielectric material provided by the invention has a relatively low dielectric constant, can meet the high-frequency application requirement of the microwave dielectric material, has relatively low dielectric loss, can effectively reduce the energy loss of a system, also has a near-zero frequency temperature coefficient, and can ensure the frequency temperature property of a product at different use temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electronic materials technology, and relates to a microwave dielectric material, its preparation method and electronic components. Background Technology

[0002] Microwaves, characterized by high frequency, short wavelength, large information capacity, strong penetration, and strong anti-interference ability, are widely used in communication, remote sensing, and satellite positioning systems. Microwave dielectric materials, as the main materials used in the fabrication of microwave devices, play a crucial role in the stability and quality of communication systems.

[0003] Typically, the performance of microwave dielectric materials is evaluated based on three core parameters: dielectric constant (εr), quality factor multiplied by frequency (Q×f), and temperature coefficient of resonant frequency (τf). εr determines the propagation speed of electromagnetic waves within the material and the scalability of the device; different εr values ​​correspond to different application scenarios. Q×f reflects the energy loss level of the material in the microwave frequency band; a higher Q×f indicates lower dielectric loss and higher system efficiency. τf characterizes the stability of the material's resonant frequency as temperature changes; a near-zero τf value ensures that the device maintains frequency stability over a wide temperature range, avoiding signal drift.

[0004] In high-frequency applications such as microwave substrates, low-εr materials offer significant advantages because they effectively weaken the electromagnetic coupling effect between the dielectric and metal electrodes, reducing signal delay and crosstalk, and increasing transmission rates. Simultaneously, to balance system energy efficiency and long-term reliability, low-εr materials also need to possess high Q×f to suppress dielectric loss and near-zero τf to improve system stability. Therefore, how to further reduce εr while effectively maintaining a high quality factor and precisely controlling τf to approach zero has become a key issue in the current research and development of microwave dielectric materials. Summary of the Invention

[0005] In view of the problems existing in the prior art, the purpose of this invention is to provide a microwave dielectric material, its preparation method, and electronic components. The microwave dielectric material simultaneously possesses a low dielectric constant, a high quality factor, and a near-zero temperature coefficient of resonant frequency.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a microwave dielectric material, wherein the raw materials for preparing the microwave dielectric material, based on a total weight of 100wt%, include the following components: 5wt%~20wt% calcium aluminum borosilicate glass, 60wt%~85wt% SiO2, and 2wt%~15wt% additives; the additives include at least one of B2O3, Li2O and Al2O3, and at least one of ZnO and TiO2.

[0008] The raw materials for preparing the microwave dielectric material described in this invention include SiO2, calcium aluminum borosilicate glass, and additives. It can be understood that after the sintering reaction during the synthesis process, it no longer contains single raw material components such as CaO, B2O3, and ZnO. These raw material components form a new and complex composition system, making the microwave dielectric material obtained in this invention a microwave dielectric ceramic material. Therefore, the characteristics of the microwave dielectric material are described based on the composition of the raw materials.

[0009] Specifically, in the raw materials for preparing the microwave dielectric material of this invention, firstly, this invention innovatively utilizes calcium aluminum borosilicate glass as a dopant, which is beneficial for improving the quality factor; secondly, SiO2, as the main material, is the core of the entire system. It exists in an amorphous form in the final microwave dielectric material and makes a major contribution to the low dielectric constant. Therefore, by controlling the amount and content of SiO2, it is beneficial for the microwave dielectric material of this invention to simultaneously achieve a low dielectric constant; thirdly, this invention uses additives with specific component combinations. The addition of at least one of B2O3, Li2O, and Al2O3 is beneficial for promoting densification, improving chemical and structural stability, and facilitating balanced synthesis. The addition of at least one of ZnO and TiO2, which improves the sinterability and final performance of the microwave dielectric material, further enhances the near-zero resonant frequency temperature coefficient of the microwave dielectric material of this invention. In particular, the appropriate addition of TiO2 can significantly enhance the near-zero adjustment of the resonant frequency temperature coefficient, ensuring the frequency stability of the device. Therefore, through the synergistic combination of the above-mentioned raw material components, a ceramic microwave dielectric material is finally obtained, which has a low dielectric constant, meeting the high-frequency application requirements of microwave dielectric materials. At the same time, it has low dielectric loss, which can effectively reduce the energy loss of the system. It also has a near-zero frequency temperature coefficient, which can ensure the frequency temperature stability of the product under different operating temperatures.

[0010] The calcium aluminum borosilicate glass of the present invention has a weight percentage of 5wt% to 20wt%, for example, it can be 5wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, or 20wt%; the SiO2 has a weight percentage of 60wt% to 85wt%, for example, it can be 60wt%, 62wt%, 64wt%, 66wt%, 68wt%, 70wt%, 72wt%, 74wt%, 76wt%, 78wt%, 80wt%, 82wt%, or 85wt%; the additives have a weight percentage of 2wt% to 15wt%, for example, it can be 2wt%, 2.2wt%, 2.6wt%, 3wt%, 3.4wt%, 4wt%, 5wt%, 6wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, or 15wt%.

[0011] In this invention, if the amount of calcium aluminum borosilicate glass is too small, it will be detrimental to obtaining a high quality factor for the microwave dielectric material. If the amount is too large, it will reduce the proportion of SiO2, which will be detrimental to obtaining a low dielectric constant for the microwave dielectric material.

[0012] The calcium aluminum borosilicate glass described in this invention is added as a raw material and can exist in the form of CaAl2B2O7 or similar forms in the final microwave dielectric material.

[0013] In some embodiments of the present invention, the additive satisfies at least one of the following conditions:

[0014] (1a) 2wt% ≤ the sum of the weight percentages of TiO2 and ZnO ≤ 10wt%. For example, it can be 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc.

[0015] (1b) 2wt% ≤ weight percentage of ZnO ≤ 10wt%. For example, it can be 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc.

[0016] (1c) 0 ≤ TiO2 weight percentage ≤ 5 wt%. For example, it can be 0 wt% (i.e., no TiO2), 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, or 5 wt%, etc.

[0017] In this invention, the amount of ZnO and TiO2 used as additives should be reasonably controlled according to actual conditions. Excessive addition can easily affect the dielectric properties of the obtained microwave dielectric material.

[0018] (1d) 0.2wt%≤The sum of the weight percentages of B2O3, Li2O and Al2O3≤8wt%. For example, it can be 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%, etc.

[0019] (1e) 0.1wt% ≤ weight percentage of B2O3 ≤ 8wt%. For example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%, etc.

[0020] (1f) 0 ≤ weight percentage of Al2O3 ≤ 3wt%. For example, it can be 0wt% (i.e., no Al2O3), 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.5wt%, 1.8wt%, 2wt%, 2.12wt%, 2.5wt%, 2.8wt%, or 3wt%, etc.

[0021] (1g) 0.1wt%≤Li2O weight percentage≤8wt%. For example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, or 8wt%, etc.

[0022] In this invention, the amount of B2O3, Li2O and Al2O3 used as additives should be reasonably controlled according to actual conditions. Excessive addition can easily affect the dielectric properties of the obtained microwave dielectric material.

[0023] (1h) Based on a total weight of 100wt%, the raw materials for preparing the calcium aluminum borosilicate glass include the following components: 30wt%~55wt% CaCO3, 5wt%~20wt% Al2O3, and 30wt%~55wt% B2O3. For example, the proportion of CaCO3 can be 30wt%, 32wt%, 35wt%, 38wt%, 40wt%, 43wt%, 45wt%, 48wt%, 50wt%, 52wt%, or 55wt%, etc.; the proportion of Al2O3 can be 5wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, or 20wt%, etc.; and the proportion of B2O3 can be 30wt%, 32wt%, 35wt%, 38wt%, 40wt%, 43wt%, 45wt%, 48wt%, 50wt%, 52wt%, or 55wt%, etc.

[0024] In this invention, the amount of raw materials used in the preparation of the calcium aluminum borosilicate glass was adjusted and controlled to modify the dielectric properties of the resulting calcium aluminum borosilicate glass, reduce its impact on microwave dielectric materials when used as a doping agent, effectively improve the quality factor of microwave dielectric materials, and facilitate the melting and preparation of calcium aluminum borosilicate glass. It is understood that CaCO3, as a raw material, reacts with other raw materials to form a complex composition system of calcium aluminum borosilicate glass, but the Ca in the calcium aluminum borosilicate glass can still be represented by the CaO component.

[0025] In some embodiments of the present invention, the microwave dielectric material satisfies at least one of the following conditions:

[0026] (2a) At a frequency of 15 GHz, the dielectric constant is <5; for example, it can be 4.9, 4.8, 4.7, 4.6, 4.5, 4.4, 4.3, 4.2, 4.1 or 4, etc.

[0027] (2b) At a frequency of 15 GHz, the dielectric loss is <1‰; for example, it can be 0.9‰, 0.8‰, 0.7‰, 0.6‰, 0.5‰, 0.4‰, 0.3‰, 0.2‰ or 0.1‰, etc.

[0028] (2c) The frequency temperature coefficient is -20ppm / ℃ to 0ppm / ℃. For example, it can be -20ppm / ℃, -18ppm / ℃, -15ppm / ℃, -13ppm / ℃, -10ppm / ℃, -8ppm / ℃, -5ppm / ℃, -4ppm / ℃, -3ppm / ℃, -2ppm / ℃, -1ppm / ℃ or -0.1ppm / ℃, etc.

[0029] (2d) Volume resistivity 0.5×10 12 Ω·cm ~8.5×10 12 Ω·cm. For example, it could be 0.5 × 10⁻⁶. 12 Ω·cm, 1×10 12 Ω·cm, 2×10 12 Ω·cm, 3×10 12 Ω·cm, 4×10 12 Ω·cm, 5×10 12 Ω·cm, 6×10 12 Ω·cm, 7×10 12 Ω·cm, 8×10 12 Ω·cm or 8.5×10 12 Ω·cm, etc.

[0030] Secondly, the present invention provides a method for preparing the microwave dielectric material described in the first aspect, the method comprising the following steps:

[0031] Calcium aluminum borosilicate glass, SiO2, and additives are mixed and ground to obtain a slurry;

[0032] After drying the slurry, a mixed powder is obtained;

[0033] The mixed powder is sintered to obtain a microwave dielectric material.

[0034] In some embodiments of the present invention, the method for preparing the calcium aluminum borosilicate glass includes: mixing the raw materials for preparing calcium aluminum borosilicate glass, and sequentially melting and quenching them to obtain calcium aluminum borosilicate glass.

[0035] In the preparation method of the microwave dielectric material described in this invention, the use of calcium aluminum borosilicate glass as a doping agent is also beneficial to reducing the sintering temperature; controlling the amount of SiO2 helps to reduce or avoid the problem of incomplete sintering; specific additives help to further reduce the sintering temperature during sintering, improve fluidity, promote densification under low-temperature sintering, and take into account both sinterability and performance optimization effects.

[0036] In some embodiments of the present invention, the method for preparing the calcium aluminum borosilicate glass satisfies at least one of the following conditions:

[0037] (3a) The raw materials for preparing the calcium aluminum borosilicate glass include CaCO3, Al2O3 and B2O3.

[0038] (3b) The process of mixing the raw materials for preparing calcium aluminum borosilicate glass includes sequential wet ball milling, heating and drying, and sieving.

[0039] For example, in some embodiments, the material may be air-dried at room temperature (20°C to 30°C) before heating and drying. In some embodiments, the heating and drying temperature is 80°C to 110°C, and the time is 1 hour to 4 hours; in some embodiments, the sieve mesh is 40 to 60 mesh, and the material passing through the sieve is collected.

[0040] (3c) The melting temperature is 1350℃~1550℃, for example, it can be 1350℃, 1365℃, 1380℃, 1400℃, 1420℃, 1450℃, 1470℃, 1500℃, 1520℃ or 1550℃, etc., and the time is 0.5~2h, for example, it can be 0.5h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2h, etc.

[0041] (3d) The quenching includes water quenching.

[0042] (3e) The quenching process yields a glassy body, which is then crushed to obtain glass powder with a particle size D50 of 1μm to 3μm. For example, the particle size can be 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, or 3μm, etc.

[0043] It should be emphasized that if calcium aluminum borosilicate glass is not prepared in advance, and instead the raw materials for preparing calcium aluminum borosilicate glass, such as CaCO3, Al2O3 and B2O3, are used as additives to directly synthesize microwave dielectric materials with SiO2 and other additives, the sintering effect will be poor, and the quality factor of the obtained microwave dielectric material cannot be effectively adjusted. That is, the effect of using calcium aluminum borosilicate glass as a doping agent in this invention cannot be achieved.

[0044] In some embodiments of the present invention, the preparation method satisfies at least one of the following conditions:

[0045] (4a) The method of mixing and grinding includes ball milling; the solvent for ball milling includes ethanol; the ball milling time is 2h to 8h. For example, it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, etc.

[0046] In the preparation method described in this invention, calcium aluminum borosilicate glass, SiO2, and additives are ground in advance to ensure that the raw material components are mixed evenly and reach a certain particle size and fineness, which is beneficial to improving the processability of subsequent granulation and molding, as well as the uniformity and sintering effect.

[0047] (4b) The drying temperature is 80℃~110℃. For example, it can be 80℃, 85℃, 90℃, 95℃, 100℃, 105℃ or 110℃, etc.

[0048] (4c) Before the sintering, the mixed powder is granulated and shaped in sequence, and then the sintering is performed.

[0049] In the preparation method described in this invention, granulation and molding allow the microwave dielectric material obtained after sintering to be directly produced as a product with a certain shape and structure, so as to match and adapt to subsequent devices. It is understood that directly sintering the mixed powder will still yield the microwave dielectric material.

[0050] (4d) The granulation process uses a binder; the binder accounts for 15wt% to 30wt% of the mass of the mixed powder. For example, it can be 15wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, or 30wt%, etc. The binder includes polymethyl methacrylate.

[0051] For example, in some embodiments, the molding material obtained by molding includes a round sample with a diameter of 10 mm to 20 mm and a thickness of 2 mm to 5 mm.

[0052] In some embodiments of the present invention, the sintering process includes first performing a debinding process at a first temperature, and then increasing the temperature to a second temperature for co-firing.

[0053] In the preparation method described in this invention, if a binder is used for granulation and molding of the mixed powder, heat treatment is first performed at a lower temperature to remove the binder and avoid its residue from affecting the performance of the microwave dielectric material.

[0054] In some embodiments of the present invention, the sintering satisfies at least one of the following conditions:

[0055] (5a) The first temperature is 400℃~500℃. For example, it can be 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃ or 500℃, etc.

[0056] (5b) The second temperature is 850℃~900℃. For example, it can be 850℃, 860℃, 870℃, 880℃, 890℃ or 900℃, etc.

[0057] (5c) The co-firing is carried out in an oxygen-containing atmosphere. Exemplarily, in some embodiments, the oxygen-containing atmosphere includes an atmospheric atmosphere.

[0058] (5d) The co-firing time is 1h to 5h. For example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, etc.

[0059] In this invention, the microwave dielectric material is prepared using a system of SiO2, calcium aluminum borosilicate glass, and specific additives. This system helps to lower the sintering temperature, enabling dense sintering at a lower co-firing temperature. A sintering temperature below 900°C can be achieved, and the microwave dielectric material obtained after low-temperature sintering still exhibits a reduced dielectric constant and a high quality factor. If calcium aluminum borosilicate glass is not used as a dopant and instead its raw materials are used in the synthesis of microwave dielectric materials in the form of oxides, the effects achieved by calcium aluminum borosilicate glass cannot be replicated.

[0060] Thirdly, the present invention provides an electronic component containing the microwave dielectric material described in the first aspect, or containing the microwave dielectric material prepared by the preparation method described in the second aspect.

[0061] For example, in some embodiments, the electronic components include filters, resonators, couplers, inductors, or capacitors.

[0062] It should be noted that, due to space limitations and to avoid redundancy, this invention does not exhaustively list all point values ​​within the above numerical range, but it is not limited to the listed values ​​either; other unlisted values ​​within the above numerical range are also applicable.

[0063] Compared with existing technical solutions, the present invention has at least the following beneficial effects:

[0064] The microwave dielectric material of the present invention is mainly composed of SiO2, calcium aluminum borosilicate glass and additives. It has a low dielectric constant, which can meet the high-frequency application requirements of microwave dielectric materials. At the same time, it has a low dielectric loss, which can effectively reduce the energy loss of the system. It also has a near-zero frequency temperature coefficient, which can ensure the frequency temperature performance of the product under different operating temperatures.

[0065] The microwave dielectric material described in this invention has a dielectric constant of less than 5, a dielectric loss of less than 1‰, and a frequency temperature coefficient of less than -20ppm / ℃ when measured at a frequency of 15GHz. It can be widely used in electronic components such as filters, resonators, couplers, inductors, and capacitors, as well as in their development and manufacturing.

[0066] The method for preparing microwave dielectric materials according to the present invention can achieve low-temperature sintering and densification at a relatively low temperature of 850℃~900℃. Detailed Implementation

[0067] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0068] Example 1

[0069] This embodiment provides a microwave dielectric material composed of the following components by weight percentage: 12.21 wt% calcium aluminum borosilicate glass A, 84.13 wt% SiO2, and 3.66 wt% additives; wherein the calcium aluminum borosilicate glass A is composed of 45.12 wt% CaCO3, 7.63 wt% Al2O3, and 47.25 wt% B2O3 by weight; the additives include B2O3, Li2O, and Al2O3 with a total weight percentage of 0.84 wt%, wherein B2O3 accounts for 0.36 wt%, Li2O accounts for 0.42 wt%, and Al2O3 accounts for 0.06 wt%; the additives also include ZnO and TiO2 with a total weight percentage of 2.82 wt%, wherein ZnO accounts for 2.52 wt% and TiO2 accounts for 0.30 wt%.

[0070] The method for preparing the microwave dielectric material includes the following steps:

[0071] (1) Preparation of calcium aluminum borosilicate glass: CaCO3, Al2O3 and B2O3 were weighed by weight percentage as raw material powder for calcium aluminum borosilicate glass A. The above components were wet ball milled for 6 hours with anhydrous ethanol as medium. After drying at room temperature, they were placed in a 90℃ oven for 2 hours. After drying, the powder was crushed and passed through a 60-mesh sieve. The sieved powder was placed in a corundum crucible and heated to 1400℃ for melting and homogenization. After holding at the temperature for 1 hour, it was poured into water for quenching to obtain glass body. The obtained glass body slag was dried and crushed and ball milled to obtain calcium aluminum borosilicate glass powder with a particle size D50 of 1.0um~3.0um.

[0072] In this embodiment, calcium aluminum borosilicate glass A is composed of 45.12 wt% CaCO3, 7.63 wt% Al2O3, and 47.25 wt% B2O3 by weight. Calcium aluminum borosilicate glass B and calcium aluminum borosilicate glass C are also prepared. Calcium aluminum borosilicate glass B is composed of 52.06 wt% CaCO3, 17.52 wt% Al2O3, and 30.42 wt% B2O3 by weight. Calcium aluminum borosilicate glass C is composed of 49.15 wt% CaCO3, 13.91 wt% Al2O3, and 36.94 wt% B2O3 by weight.

[0073] (2) The calcium aluminum borosilicate glass powder obtained in step (1) is mixed with SiO2 and additives, and planetary ball milled for 5 hours with anhydrous ethanol as solvent. The uniformly mixed slurry is taken out and dried in an oven at 95°C to obtain mixed powder. The dried mixed powder is weighed and 23wt% of binder PMMA is added for granulation and dry pressing to obtain a round sample with a diameter of 14mm and a thickness of 3.5mm. The round sample is sintered, specifically by first debinding at 450°C and then sintering in an atmospheric atmosphere at 900°C for 2 hours to produce an ultra-low dielectric and low loss microwave dielectric material.

[0074] Examples 2 to 10, Comparative Examples 1 and 2

[0075] Other embodiments and comparative examples are based on Example 1, but differ from Example 1 in at least one of the following: the type of calcium aluminum borosilicate glass, its weight percentage in the raw materials for preparing microwave dielectric materials, or the weight percentage of SiO2 and additives (keeping the mass ratio between the additives constant), as shown in Tables 1 and 2.

[0076] Table 1

[0077]

[0078] Table 2

[0079]

[0080] Characterization and testing:

[0081] The microwave dielectric materials obtained in the above embodiments and comparative examples were tested as follows:

[0082] The dielectric properties of microwave dielectric materials are tested using a vector network analyzer. Before testing, the diameter D and thickness h of the sample are measured for use in testing the dielectric constant and quality factor. When testing the frequency temperature coefficient, the equipment needs to be heated to 25℃ and 85℃ respectively. After the temperature stabilizes, the resonant peaks of the sample at 25℃ and 85℃ are measured, and the center frequency f0 is recorded, denoted as f0. 25 and f 85 Then, calculate the temperature coefficient of frequency of the material using the following formula:

[0083]

[0084] Volume resistivity was tested using an insulation resistance tester, and the test standard referred to was GJB 360B-2009.

[0085] The test results are shown in Tables 3 and 4.

[0086] Table 3

[0087]

[0088] Table 4

[0089]

[0090] Combining Tables 3 and 4, we can see that:

[0091] A comparison of Examples 1 to 16 and Comparative Examples 1 to 3 revealed that the microwave dielectric material of the present invention exhibits a dielectric constant of less than 5, a dielectric loss of less than 1‰, and a frequency temperature coefficient within -20ppm / ℃ at a frequency of 15GHz. The raw material components for preparing the microwave dielectric material of the present invention mainly consist of SiO2, calcium aluminum borosilicate glass, and additives. The use of calcium aluminum borosilicate glass helps improve the quality factor, thereby reducing dielectric loss. Controlling the content ratio of SiO2 helps to achieve a lower dielectric constant. The use of additives, especially controlling the content ratio of ZnO and TiO2, further facilitates obtaining a near-zero frequency temperature coefficient. In summary, by controlling the proportions of SiO2, calcium aluminum borosilicate glass, and additives, and through the synergistic combination of these components, microwave dielectric materials can simultaneously possess low dielectric constants, meeting the requirements for high-frequency applications, low dielectric loss, effectively reducing system energy loss, and a near-zero temperature coefficient of frequency, ensuring the frequency-temperature stability of the product under different operating temperatures. This microwave dielectric material can be widely used in the development and manufacturing of electronic components such as filters, resonators, couplers, inductors, and capacitors.

[0092] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0093] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0094] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A microwave dielectric material, characterized in that, Based on a total weight of 100wt%, the raw materials for preparing the microwave dielectric material include the following components: 5wt%~20wt% calcium aluminum borosilicate glass, 60wt%~85wt% SiO2, and 2wt%~15wt% additives; the additives include at least one of B2O3, Li2O and Al2O3, and at least one of ZnO and TiO2.

2. The microwave dielectric material according to claim 1, characterized in that, The additive satisfies at least one of the following conditions: (1a) 2wt% ≤ the sum of the weight percentages of TiO2 and ZnO ≤ 10wt%; (1b) 2wt% ≤ ZnO weight percentage ≤ 10wt%; (1c) 0 ≤ TiO2 weight percentage ≤ 5 wt%; (1d) 0.2wt%≤Sum of the weight percentages of B2O3, Li2O and Al2O3≤8wt%; (1e) 0.1wt% ≤ B2O3 weight percentage ≤ 8wt%; (1f) 0 ≤ Al2O3 weight percentage ≤ 3wt% (1g) 0.1wt% ≤ Li2O weight percentage ≤ 8wt%; (1h) The raw materials for preparing the calcium aluminum borosilicate glass, based on a total weight of 100wt%, include the following components: 30wt%~55wt% CaCO3, 5wt%~20wt% Al2O3, and 30wt%~55wt% B2O3.

3. The microwave dielectric material according to claim 1 or 2, characterized in that, The microwave dielectric material satisfies at least one of the following conditions: (2a) At a frequency of 15 GHz, the dielectric constant is <5; (2b) At a frequency of 15 GHz, the dielectric loss is <1‰; (2c) The frequency temperature coefficient is -20ppm / ℃ to 0ppm / ℃; (2d) Volume resistivity 0.5×10 12 Ω·cm ~8.5×10 12 Ω·cm.

4. A method for preparing a microwave dielectric material according to any one of claims 1-3, characterized in that, The preparation method includes the following steps: Calcium aluminum borosilicate glass, SiO2, and additives are mixed and ground to obtain a slurry; After drying the slurry, a mixed powder is obtained; The mixed powder is sintered to obtain a microwave dielectric material.

5. The method for preparing microwave dielectric material according to claim 4, characterized in that, The method for preparing the calcium aluminum borosilicate glass includes: mixing the raw materials for preparing calcium aluminum borosilicate glass, and sequentially melting and quenching them to obtain calcium aluminum borosilicate glass.

6. The method for preparing microwave dielectric material according to claim 5, characterized in that, The method for preparing the calcium aluminum borosilicate glass satisfies at least one of the following conditions: (3a) The raw materials for preparing the calcium aluminum borosilicate glass include CaCO3, Al2O3 and B2O3; (3b) The process of mixing the raw materials for preparing calcium aluminum borosilicate glass includes sequential wet ball milling, room temperature drying, heating and drying, and sieving; (3c) The melting temperature is 1350℃~1550℃, and the melting time is 0.5~2h; (3d) The quenching includes water quenching; (3e) The quenching process yields a glassy body, which is then crushed to obtain a particle size D. 50 It is a glass powder with a particle size of 1μm to 3μm.

7. The method for preparing microwave dielectric material according to claim 4, characterized in that, The preparation method satisfies at least one of the following conditions: (4a) The method of mixing and grinding includes ball milling; the solvent for ball milling includes ethanol; the ball milling time is 2h to 8h; (4b) The drying temperature is 80℃~110℃; (4c) Before the sintering, the mixed powder is granulated and shaped in sequence, and then the sintering is performed; (4d) The granulation uses a binder; the mass of the binder accounts for 15wt% to 30wt% of the mass of the mixed powder; the binder includes polymethyl methacrylate.

8. The method for preparing microwave dielectric material according to claim 4, characterized in that, The sintering process includes first performing a debinding process at a first temperature, and then raising the temperature to a second temperature for co-firing.

9. The method for preparing microwave dielectric material according to claim 8, characterized in that, The sintering satisfies at least one of the following conditions: (5a) The first temperature is 400℃~500℃; (5b) The second temperature is 850℃~900℃; (5c) The co-firing is carried out in an oxygen-containing atmosphere; (5d) The co-firing time is 1h~5h.

10. An electronic component, characterized in that, The microwave dielectric material comprising any one of claims 1-3, or the microwave dielectric material prepared by any one of claims 4-9.